Determining the appropriate concentration of an anesthetic mixture in three different fish species with the PROMETHEE decision model - Minaz, Mert; Er, Akif; Ak, Kübra; Kurtoğlu, İlker Zeki; Kayış, Şevki (Frontiers in Veterinary Science, 2024)
Anesthesia is applied to protect fish welfare for reducing employee workload in aquaculture. The efficacy of the anesthetic agent varies depending on the fish species. In this study, the effect of a commercial anesthetic (VetiVital AquaSED) manufactured mainly with herbal extracts (includes eugenol, linalool, linalyl acetat etc.) on three different fish species (rainbow trout, common carp, and Danube sturgeon) was investigated. In addition, the best available concentration of the anesthetic mixture for each species was determined using the PROMETHEE decision model. Danube sturgeon showed more resistance to anesthetics than the other two species. It was determined that the increase in concentration caused histological deterioration in fish. On the other hand, hematological parameters were affected by the anesthetic mixture, and this effect returned to normal levels after 8 h. According to the multi-criteria decision model, the best available concentrations determined by considering 10 different criteria are 400, 480, and 675 mg L−1 for rainbow trout, common carp and Danube sturgeon, respectively. Future studies should focus on developing the most appropriate anesthesia mixture in terms of physiological and anesthesia effectiveness for the target fish species.